2004
DOI: 10.1007/s00011-004-1247-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of histamine H1-receptor enhances neurotrophic factor secretion from cultured astrocytes

Abstract: Our results indicate that histamine H(1)-receptor and PKC are involved in the signal transduction pathway, responsible for histamine-stimulated NGF secretion from cultured astrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…The staining indicated that more than 90 % of the cells in our experimental model were astrocytes, which repeats our previous purity results (29).…”
Section: Preparation Of Astrocyte Culturessupporting
confidence: 74%
“…The staining indicated that more than 90 % of the cells in our experimental model were astrocytes, which repeats our previous purity results (29).…”
Section: Preparation Of Astrocyte Culturessupporting
confidence: 74%
“…DRG cultures were serum-deprived and treated with either 10 M histamine (a stimulant of NGF secretion) or 10 M ATP␥S for 24 h. NGF concentrations in conditioned medium prepared from DRG cultures were measured in triplicate by ELISA (R&D Systems, Minneapolis, MN) as previously described (Lipnik-Stangelj and Carman-Krzan, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…org as supplemental material) and found that the concentration of NGF was Ͻ80 pg/ml after 72 h growth in serum-containing medium. Serum starvation, alone or together with ATP␥S, did not stimulate NGF secretion, whereas histamine, a known stimulator of NGF secretion (Lipnik-Stangelj and Carman-Krzan, 2004), significantly ( p Ͻ 0.01) increased NGF concentrations in DRG cultures (supplemental Fig. 2, available at www.jneurosci.org as supplemental material).…”
Section: P2y 2 Activation In Drg Neurons Inhibits Apoptosis Independementioning
confidence: 99%
“…After the cell cultures became confluent (12-14 days), the cells were treated with 1 mM histamine (Sigma Chemical Co., St. Louis) and 10 ng/ml recombinant rat IL-6 (R&D Systems, Minneapolis) for 24 h. In additional experiments, cells were pre-treated with 1 mM histamine for 24 h, and than incubated in the presence of 10 ng/ml IL-6, for the next 24 h. The concentrations of histamine and IL-6 used in the experiment were chosen from dose-response curves obtained in our previous studies [4,7]. After treatment, culture medium was collected and NGF levels determined.…”
Section: Methodsmentioning
confidence: 99%